1999
DOI: 10.1039/a808699k
|View full text |Cite
|
Sign up to set email alerts
|

The temperature-induced changes in hydrogen bonding of decan-1-ol in the pure liquid phase studied by two-dimensional Fourier transform near-infrared correlation spectroscopy

Abstract: Fourier transform near-infrared (FT-NIR) spectra of decan-1-ol in the pure liquid phase were investigated in the regions of the Ðrst and second overtones of the OH stretching vibration over the temperature range 15È76 ¡C. The dynamics of temperature-induced changes in the hydrogen bonding were explored by the 2D correlation approach. It was found that the Ðrst overtone of the monomer band is split into two peaks (7087 and 7114 cm~1). The peaks originate from the rotational isomerism of the OH group. Although t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 19 publications
4
43
1
Order By: Relevance
“…2-methylpropan-2-ol. Czarnecki et al 6 have also postulated the same order of the self-association for the three kinds of butanols. In addition, it should be noted that the peak positions of the bands due to the free OH groups for the three kinds of butanols are slightly different from each other: 1407 nm (7107 cm 2 1 ) for butan-1-ol, 1411 nm (7087 cm 2 1 ) for butan-2-ol, and 1415 nm (7067 cm 2 1 ) for 2-methylpropan-2-ol, respectively.…”
Section: Resultsmentioning
confidence: 80%
“…2-methylpropan-2-ol. Czarnecki et al 6 have also postulated the same order of the self-association for the three kinds of butanols. In addition, it should be noted that the peak positions of the bands due to the free OH groups for the three kinds of butanols are slightly different from each other: 1407 nm (7107 cm 2 1 ) for butan-1-ol, 1411 nm (7087 cm 2 1 ) for butan-2-ol, and 1415 nm (7067 cm 2 1 ) for 2-methylpropan-2-ol, respectively.…”
Section: Resultsmentioning
confidence: 80%
“…For example, temperature-dependent NIR spectra of decanol for hydrogen bonding study and rotational isomerism detection were reported by Czarnecki et al [122]. Temperature-dependent NIR of hydrogen-bonded octanol for second overtones, indicating the presence of dimers, and splitting of monomer bands due to conformers were also studied [123].…”
Section: Associated Liquids and Hydrogen Bondingmentioning
confidence: 94%
“…A number of QM studies on NIR spectra of basic molecules have been reported over the last few years (Beć et al, 2016a, 2018a; Grabska et al, 2017a,b). Vibrational studies of these systems are relatively important for our understanding of the general spectra-structure correlations (Czarnecki et al, 2000; Wojtków and Czarnecki, 2006; Michniewicz et al, 2007, 2008; Haufa and Czarnecki, 2010) and the role of conformational isomerism (Czarnecki et al, 2006; Wojtków and Czarnecki, 2006), structure and dynamics of hydrogen-bonding, self-association mechanisms and intermolecular interactions (Czarnecki and Ozaki, 1999; Czarnecki et al, 2000, 2010; Czarnecki, 2003; Czarnecki and Wojtków, 2004; Michniewicz et al, 2007; Haufa and Czarnecki, 2010), in particular the interactions with solvent molecules (e.g., water, nonpolar solvents) (Gonjo et al, 2011; Tomza and Czarnecki, 2015), or chiral discrimination (Czarnecki, 2003); the temperature influence on the above effects was often also examined (Czarnecki and Ozaki, 1999; Iwahashi et al, 2000; Šašić et al, 2002; Wojtków and Czarnecki, 2005, 2006, 2007; Grabska et al, 2017a). In the above contexts, alcohol molecules have remained among those investigated most frequently in physicochemical NIRS; often, the lack of QM spectra simulations hindered full comprehension therein.…”
Section: Theoretical Near-infrared Spectroscopy–an Overview Of the Emmentioning
confidence: 99%
“…NIRS manifests unique suitability for investigating intermolecular interactions, e.g., hydrogen-bonding. Not without reason, this aspect is strongly focused in physicochemical NIRS (Czarnecki and Ozaki, 1999; Czarnecki et al, 2000, 2010; Czarnecki, 2003; Czarnecki and Wojtków, 2004; Michniewicz et al, 2007; Gonjo et al, 2011; Tomza and Czarnecki, 2015). The potential of QM simulations has long been utilized in MIR and Raman studies.…”
Section: Theoretical Near-infrared Spectroscopy–an Overview Of the Emmentioning
confidence: 99%